2013
DOI: 10.1242/jcs.122705
|View full text |Cite
|
Sign up to set email alerts
|

P2 receptor networks regulate signaling duration over a wide dynamic range of ATP concentrations

Abstract: SummaryThe primordial intercellular signaling molecule ATP acts through two families of cell-surface P2 receptors -the P2Y family of Gprotein-coupled receptors and the P2X family of ligand-gated cation channels. Multiple P2 receptors are expressed in a variety of cell types. However, the significance of these networks of receptors in any biological system remains unknown. Using osteoblasts as a model system, we found that a low concentration of ATP (10 mM, ATP low ) induced transient elevation of cytosolic Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 65 publications
(73 reference statements)
1
67
0
Order By: Relevance
“…Data are means ± SEM (n = 3 independent preparations) alone, or more so by a combination of Wnt3a and BzATP, was associated with enhanced transcriptional activity. These observations are consistent with our previous findings, in which we demonstrated that prolonged but not transient Ca 2+ /NFATc1 signaling in osteoblasts resulted in increased expression of NFAT target genes [23]. Taken together, these findings highlight the positive association between duration of nuclear occupancy by a transcription factor (such as NFAT or β-catenin) and expression of its target genes.…”
Section: P2x7 Potentiates the Wnt/β-catenin Pathwaysupporting
confidence: 93%
See 2 more Smart Citations
“…Data are means ± SEM (n = 3 independent preparations) alone, or more so by a combination of Wnt3a and BzATP, was associated with enhanced transcriptional activity. These observations are consistent with our previous findings, in which we demonstrated that prolonged but not transient Ca 2+ /NFATc1 signaling in osteoblasts resulted in increased expression of NFAT target genes [23]. Taken together, these findings highlight the positive association between duration of nuclear occupancy by a transcription factor (such as NFAT or β-catenin) and expression of its target genes.…”
Section: P2x7 Potentiates the Wnt/β-catenin Pathwaysupporting
confidence: 93%
“…Additionally, BMP-2 has been shown to stimulate β-catenin transcriptional activity leading to increased expression of Wnt ligands and their receptors in differentiating cultures of calvarial osteoblasts [36]. Previously, we demonstrated that prolonged Ca 2+ /NFATc1 signaling downstream of P2X7 leads to expression of cyclooxygenase-2 (COX-2) [23]. Interestingly, NFATc1 has been shown to function downstream of strontium ranelate in vitro to elicit expression of canonical Wnt3a [37].…”
Section: P2x7 Potentiates the Wnt/β-catenin Pathwaymentioning
confidence: 98%
See 1 more Smart Citation
“…Compared with other P2X receptor subtypes, significantly higher ATP concentrations are required for P2X 7 receptor activation. 35,36 Although such high ATP concentrations are typically not produced under physiologic conditions, moderate levels of extracellular ATP may play a role in mechanotransduction in a variety of tissues. 36 Moreover, significant release of ATP occurs from stressed, ischemic, hypoxic, or traumatized tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular calcium oscillations are known to occur during a number of processes including embryogenesis and the associated signals are implicated in cell differentiation (Tonelli et al, 2012). These autocrine and paracrine functions involve the calcium-dependent transcription factor nuclear factor of activated T cells (NFAT), which is known to be induced by extracellular nucleotides, at least in microglia, human MSCs and osteoblasts (Shiratori et al, 2010; Glaser et al, 2013; Grol et al, 2013). NFAT activation is critical for gene regulation because it is activated during differentiation of thymocytes and may have an integral role in hematopoietic cell growth and differentiation (Adachi et al, 2000).…”
Section: Calcium Oscillations Mesenchymal and Hematopoietic Stem Cellsmentioning
confidence: 99%